The regioselective synthesis of spirooxindolo pyrrolidines and pyrrolizidines via three-component reactions of acrylamides and aroylacrylic acids with isatins and α-amino acids - Pavlovskaya, Tatyana L.; Yaremenko, Fedor G.; Lipson, Victoria V.; Shishkina, Svetlana V.; Shishkin, Oleg V.; Musatov, Vladimir I.; Karpenko, Alexander S. (Beilstein Journal of Organic Chemistry, 2014)
The regioselective three-component condensation of azomethine ylides derived from isatins and α-amino acids with acrylamides or aroylacrylic acids as dipolarophiles has been realized through a one-pot 1,3-dipolar cycloaddition protocol. Decarboxylation of 2'-aroyl-2-oxo-1,1',2,2',5',6',7',7a'-octahydrospiro[indole-3,3'-pyrrolizine]-1'-carboxylic acids is accompanied by cyclative rearrangement with formation of dihydropyrrolizinyl indolones.
Keywords: acrylamides; aroylacrylic acids; azomethine ylide; cyclative rearrangement; cycloaddition; multicomponent; spirooxindoles